The effect of a stability and coordination training programme on balance in older adults with cardiovascular disease: a randomised exploratory study. (December 2019) - Segev, Daria; Hellerstein, Devora; Carasso, Rafi; Dunsky, Ayelet
Background: Cardiovascular diseases are considered a leading factor in mortality and morbidity. The older adult population with cardiovascular diseases has a higher risk of falls as compared to a matched age healthy population. Objective: To investigate the effect of stability and coordination training within a cardiac rehabilitation programme on fall risk in older adults with cardiovascular diseases enrolled in cardiac rehabilitation. Methods: Twenty-six people with cardiovascular diseases (age 74±8) were divided randomly into intervention and control groups. The intervention group received 20 min of stability and coordination exercises as part of their 80 min cardiac rehabilitation programme, while the control group performed the traditional cardiac rehabilitation programme, twice a week, for 12 weeks. Balance assessment was based on three tests: the Timed Up and Go, Functional Reach and Balance Error Scoring System, which were measured twice before the intervention, once following the intervention and once four weeks after the termination of the intervention. A two-way analysis of variance (group × time) with repeated measures was performed to examine differences between groups and between assessments. Results: Seventy per cent of participants in the intervention group adhered to the programme, with significant improvement post-intervention in the Timed Up and Go ( p < .01) and the Balance Error Scoring System ( p < .05) with no changes among the control group. Discussion: Stability and coordination training alongside a traditional cardiac rehabilitation programme may improve static and dynamic balance, and muscle strength, skills that are considered major components in postural control. Clinicians who work in cardiac rehabilitation centres should consider including this training alongside the routine cardiac rehabilitation programme.